Swedish journalist 2011 - Asp, Kent (University of Gothenburg, 2013)
The Swedish journalist survey is conducted at the Dept of Journalism, Media and Communication (JMG) at the University of Gothenburg. The questionnaire is submitted to 2 500 randomly selected journalists from all over Sweden.

The purpose of the study is to investigate how Swedish journalists perceive themselves and society, their professional role and work situation, the problems related to their code of professional ethics and the developments in the media sector.

Journalist´11 is JMG’s sixth survey. The first one was conducted in 1989. The results from the last survey, Journalist ´05, are present in the book 'Den svenska journalistkåren'.

The primary purpose of Journalist´11 is to follow up previous studies and provide a broad view of the changes that have taken place among the Swedish journalists during the last two decades. Many of the questions in the 2011 survey are therefore the same as previous years surveys.

The Swedish media system has changed dramatically since 1989. The state’s broadcast media monopoly has been abolished, commercial radio and TV, the Internet and a number of new media have emerged, and the work methods have changed, largely as a result of new technologies becoming available.

The main purpose of the journalist surveys is to investigate in a broad perspective which changes Swedish journalists have gone through during this reformation of the Swedish media landscape. Many questions asked as part of the survey are therefore the exact same as those asked in the very first survey in 1989. The long duration of the study is unique, both nationally and internationally.

Purpose:

The purpose of the study is to investigate how Swedish journalists perceive themselves and society, their professional role and work situation, the problems related to their code of professional ethics and the developments in the media sector.

Journalist´11 är en vetenskaplig frågeundersökning som genomförs vid Institutionen för journalistik, medier och kommunikation, Göteborgs universitet (JMG). Formuläret går ut till 2 500 slumpmässigt valda journalister i hela Sverige.

Undersökningen syftar till att belysa hur svenska journalister ser på sig själva och samhället, sin yrkesroll, arbetssituation och medieutvecklingen.

Journalist´11 är den sjätte undersökningen som genomförts vid JMG. Den första gjordes 1989. Resultaten från den senaste undersökningen Journalist´05 presenterades bland annat i boken Den svenska journalistkåren. Undersökningsserien har även resulterat i ett flertal doktorsavhandlingar i universitetsämnet journalistik.

Under de tjugotvå år som gått sedan 1989 har det svenska mediesystemet förändrats i grunden. Etermediemonopolet har avskaffats, kommersiell radio och TV har vuxit fram, Internet och nya medier har kommit till, arbetssätt har förändrats och påverkats av nya tekniker. Och under senare år har de sociala mediernas roll i journalistiken fått särskild uppmärksamhet.

Det främsta syftet med Journalist´11 är att följa upp tidigare undersökningar och ge en bred belysning av vilka förändringar som ägt rum i journalistkåren under de två senaste decennierna. Många frågor i Journalist´11 är därför desamma som ställts i tidigare undersökningar.

Likalydande frågor ställs också till allmänheten, och till riksdagsledamöter. Jämförelser görs med SOM-institutets undersökning 2011 och med Riksdagsenkät 2010. Även i dessa fall görs jämförelser bakåt i tiden med Journalist´89 som startpunkt.

Den långa undersökningsserien är unik, även i ett internationellt perspektiv. En motsvarande undersökningsserie finns endast i USA.

Syfte:

Undersökningen syftar till att belysa hur svenska journalister ser på sig själva och samhället, sin yrkesroll, arbetssituation och medieutvecklingen.
Journalist 2011
Keywords: mass media; massmedia; occupations; yrken; professional ethics; yrkesetik; journalism; journalistik; occupational life; yrkesliv; professional associations; yrkesföreningar; journalists; journalister; Media; Media; Information society; Informationssamhället; Working conditions; Arbetsförhållanden; Social Sciences; Samhällsvetenskap; Media and Communications; Medie-, kommunikations-, och informationsvetenskaper